Association of a Common Variant at 10q26 and Benign Prostatic Hyperplasia Aggressiveness in Han Chinese Descent - Xin Gu; Tao Huang; Ding Xu; Liujian Duan; Yang Jiao; Jian Kang; S. Lilly Zheng; Jianfeng Xu; Jielin Sun; Jun Qi (Biochemistry Research International)
Recent studies reported that rs2252004 at 10q26 was significantly associated with prostate cancer (PCa) risk in a Japanese population and was subsequently confirmed in a Chinese population. We aimed to assess the relationship between this locus and risk/aggressiveness of benign prostatic hyperplasia (BPH). The current study included 426 BPH cases and 1,008 controls from Xinhua Hospital in Shanghai, China. All BPH patients were treated with α-adrenergic blockers and 5α-reductase inhibitors for at least 9 months. Associations between rs2252004 and BPH risk/aggressiveness were tested using logistic regression. Associations between rs2252004 and clinical parameters including International Prostate Symptom Score (IPSS), total prostate volume (TPV), total PSA (tPSA), and free PSA (fPSA) were evaluated by linear regression. Allele “A” in rs2252004 was significantly associated with increased risk for aggressiveness of BPH in a Chinese population (OR = 1.42, 95% CI: 1.04–1.96, P=0.03). Patients with the genotype “A/A” (homozygous minor allele) had an increase of IPSS and TPV after treatment (P=0.045 and 0.024, resp.). No association was observed between rs2252004, BPH risk, and baseline clinicopathological traits (All P>0.05). Our study is the first to show that rs2252004 at 10q26 was associated with BPH aggressiveness and efficacy of BPH treatment.